[RETRACTED] KARAKTERISTIK MINUMAN SINBIOTIK SOYGHURT KEDELAI KUNING (Glycine max) DAN KEDELAI HITAM (Glycine soja L.) DENGAN PENAMBAHAN INULIN PADA KONSENTRASI YANG BERBEDA - Santosa, Arif Prashadi; Afifah, Dini Nur; Purnawanto, Agus Mulyadi (Jurnal Gizi dan Pangan Soedirman, 2022)
Synbiotic drinks are beverages that contain probiotic bacteria as well as prebiotics as a substrate for probiotic bacteria. This study aims to determine the type of soybean, the concentration of inulin, and the interactions that affect the proximate and organoleptic characteristics of soyghurt synbiotics. The research was conducted at the basic Agrotechnology Laboratory, Faculty of Agriculture and Fisheries, Universitas Muhammadiyah Purwokerto, from April to June 2022. This study used a Completely Randomized Design (CRD) of two factors. The first factor is soybean type: Yellow soybean (Glycine max) not peeled (K1), yellow soybean (Glycine max) peeled (K2), black soybean (Glycine Soja L.) peeled (K3), and black soybean (Glycine Soja L.) not peeled (K4). The second factor was the concentration of Inulin: 0% (I0), 3% (I1), 5% (I2), and 7% (I3). Observation variables measured pH, water content, protein content, ash content, carbohydrate content, fat content, fiber content, lactic acid bacteria viability test, antioxidant and organoleptic activity. The results showed that K4I3 (unpeeled black soybean) between soybean type and inulin concentration affected the proximate and organoleptic characteristics. The values were pH 4.30, water content 84.29, protein 6.29, ash content 0.21, carbohydrates 8 .32, fat 0.89, fiber 12.39, BAL 25x108 CFU/ml, antioxidant 50.93, color 3.95 (Neutral), aroma 4.5 (Neutral), taste 4.4 (Neutral), Softness 4 .3 (Neutral) and a total of 4.25 (Neutral).